Stress among staff nurses: A hospital-based study - Nandita Kshetrimayum; Darshana Bennadi; Sibyl Siluvai (Wolters Kluwer Medknow Publications, 2019)
Background: Stress can be described as a dynamic and reciprocal relationship between the person and the environment. Nursing is an occupation with a constellation of circumstances leading to stress. Work-related stress (occupational stress) can be damaging to a person's physical as well as mental status, which directly and indirectly affecting their quality and productivity of work. Hence, an attempt has been made with an aim to assess stress-perceived stress among staff nurses in Mysore city, India. Methodology: The descriptive cross-sectional study was conducted among 500 staff nurses selected from eight hospitals in Mysore City, India, using multistage sampling technique. Study duration was 5-month period and response rate was 100%. A structured questionnaire was administered to assess stress using Perceived Stress Scale (PSS) and Expanded Nursing Stress Scale (ENSS). Results: A cross-sectional study consisted of 500 staff nurses. Majority of the participants (467 [93.4%]) had diploma and 454 (90.8%) nurses worked on day shift. Nearly 277 (55.4%) had a moderate level of perceived stress and 249 (49.8%) had moderate occupational stress. Significant positive correlation (r = 0.144, P < 0.001) between ENSS and PSS. Conclusion: A positive correlation was found between perceived stress and occupational stress among staff nurses of Mysore City. This shows that those with general stress also have occupational stress.